Potensi kerusakan lingkungan perairan laut akibat pengoperasian alat tangkap sondong di kecamatan Concong Kabupaten Indragiri Hilir - Gusti Indra; Nofrizal Nofrizal; Viktor Amrifo (Pelantar Press, 2019)
Based on the research that has been carried out, the extent of potential damage to marine waters due to the operation of the sondong is directly proportional to the length of the operation time, the size of the sondong, the sweep length and the number of back and forth fishing gear. The longer the operating time, the larger the fishing gear size, the wider the sweep area and the greater the number of fishing gear settings (back and forth), the greater the potential for damage to marine waters. The catch consists of 37 species (including garbage), 2 types of main catch species (maincatch), 15 types of bycatch species and 20 species (including waste) from discard. Percentage of catch based on number (head) for main catch is 38%, bycatch 11% and bycatch 51%. Percentage of catch based on weight (kg) is for main catch 22%, bycatch 6% and waste catch 72%. The captured waste that is not valued is thrown away both alive and dead will become waste, this has triggered serious conservation problems due to the waste of valuable natural resources and causes populations of species to be endangered and even extinct. It can be said that there are no social, economic and conflict impacts that arise in the aquatic environment due to the operation of the fishing gear. Socially, the operation of the sondong fishing gear in the waters of the research location is acceptable, the decrease in fishermen's income and the (economic) catch in general is not due to the operation of the sondong fishing gear.